A one-pot direct regioselective iodination of Fischer-Borsche product using periodic acid in PEG-400. Issue 15 (11th April 2019) - Ghom, Monica H.; Naykode, Mahavir S.; Humne, Vivek T.; Lokhande, Pradeep D.
Graphical abstract: Highlights: Iodination is a well-known process used for the various organic transformations. Direct regioselective iodination and dehydrogenation was achieved in one-pot. The present method is metal-free and greener. Various novel iodo-substituted benzo[ a ]carbazoles have been synthesized. Resulting 5-iodo-benzo[ a ]carbazoles could have valuable significant in organic chemistry and material chemistry. Abstract: A metal-free and greener approach for the one-pot direct iodination and dehydrogenation of dihydrobenzo[ a ]carbazoles has been developed using periodic acid in polyethylene glycol-400 (PEG-400) under mild condition. This method has been proven to be tolerate to a broad range of functional groups, with good to excellent yields include metal-free inexpensive catalyst, easy work-up, benign reaction condition and high regioselectivity. The solvent has been successfully recycled up to 5 times without any loss of activity in an aqueous medium.